# How do you multiply # (-3-i)(4+2i) # in trigonometric form?

##### 1 Answer

Jan 22, 2016

#### Explanation:

Multiply out brackets (distributive law ) -using FOIL method.

# (-3 - i )(4 + 2i ) = - 12 -6i - 4i -2i^2 # [

# i^2 = -1 ] # hence

# - 12 -10i + 2 = -10 - 10i color(black)(" is the result ") # To convert to trig form require to find modulus r , and

argument,#theta # r =

# sqrt( (-10)^2 + (-10)^2 ) = sqrt200 =10sqrt2# and

#theta = tan^-1 ((-10)/-10) = tan^-1 (1 )= pi/4 # in trig form :

# 10sqrt2 (cos(pi/4) + isin(pi/4))#